Functional Bashing!

Calculus Level 3

If f f is a function such that f ( x + y ) = f ( x ) + f ( y ) f ( x ) f ( y ) f(x+y)=f(x)+f(y)-f(x)f(y) and f ( 0 ) = 1 f'(0)=-1 . Evaluate 0 1 f ( x ) d x \displaystyle \int_0^1f(x)\ dx .


The answer is -0.71828182846.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Putting x = y x=y ,

f ( 2 x ) = 2 f ( x ) [ f ( x ) ] 2 f(2x)=2f(x)-[f(x)]^2

Since it has been given that f ( 0 ) = 1 \displaystyle f'\left(0\right)=-1 , it means that the function is atleast once differentiable. Therefore, differentiating both sides, we have:

2 f ( 2 x ) = 2 f ( x ) 2 f ( x ) f ( x ) \large \displaystyle 2f'(2x)=2f'(x)-2f(x)f'(x)

2 f ( 0 ) = 2 f ( 0 ) 2 f ( 0 ) f ( 0 ) 2 ( 1 ) = 2 ( 1 ) 2 f ( 0 ) ( 1 ) f ( 0 ) = 0 \large \displaystyle \implies 2f'(0)=2f'(0)-2f(0)f'(0) \implies 2(-1)=2(-1)-2f(0)(-1) \implies \boxed{f(0) = 0}

Now, obtain the derivative of f f using first principle:

f ( x ) = lim h 0 f ( x + h ) f ( x ) h = lim h 0 f ( x ) + f ( h ) f ( x ) f ( h ) f ( x ) h = ( 1 f ( x ) ) lim h 0 f ( h ) h = ( 1 f ( x ) ) lim h 0 f ( h ) f ( 0 ) h 0 = ( 1 f ( x ) ) f ( 0 ) = f ( x ) 1 \large \displaystyle f'(x) = \lim_{h \to 0} \frac{f\left(x+h\right)-f\left(x\right)}{h} = \lim_{h \to 0} \frac{f\left(x\right)+f\left(h\right)-f\left(x\right)f\left(h\right)-f\left(x\right)}{h} = (1 - f(x)) \lim_{h \to 0} \frac{f\left(h\right)}{h} = (1 - f(x)) \lim_{h \to 0} \frac{f\left(h\right)-f\left(0\right)}{h-0} = (1 - f(x)) f'(0) = f(x) - 1

f ( x ) = f ( x ) 1 \large \displaystyle \implies f'(x) = f(x) - 1

Solving this differential equation,

d f ( x ) f ( x ) 1 = d x ln ( f ( x ) 1 ) = x + C f ( x ) = C e x + 1 = C e x + 1 \large \displaystyle \implies \frac{df\left(x\right)}{f\left(x\right)-1}=dx \implies \ln\left(f\left(x\right)-1\right)=x+C \implies f\left(x\right)=C'e^x+1=Ce^x+1

Since f ( 0 ) = 0 \large \displaystyle f(0) = 0 , C = 1 \large \displaystyle C=-1 . Therefore, f ( x ) = 1 e x \large \displaystyle \boxed{f(x) = 1 - e^x} .

0 1 1 e x d x = 2 e \large \displaystyle \large \displaystyle \int_0^1 1 - e^x dx = \boxed{2-e}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...